Multifocal Subcutaneous and Muscular Tuberculosis in a Young Immunocompetent Man: A Case Report and Literature Review - Cabo, João (2020)
Due to unfavorable conditions for survival and multiplication of Mycobacterium tuberculosis, muscle and soft tissue involvement is probably the rarest form of presentation of musculoskeletal tuberculosis, particularly without a clinically or radiologically apparent primary focus. As in other extrapulmonary forms of tuberculosis, its relative incidence is higher among immunocompromised patients. A progressive swelling is the most common complaint at presentation, which is otherwise mild and nonspecific. We present a case of multifocal (seven) subcutaneous and muscular tuberculous abscesses in a 29-year-old Indian patient who had no apparent underlying risk factors, nor any other organ involvement. Provisional diagnosis was initially made upon Mycobacterium tuberculosis complex nucleic acid detection in an aspirate of one of the collections and later confirmed by a positive culture on Lowenstein-Jensen medium. Two abscesses required aspiration and two others drained spontaneously. The patient responded well to nine months of anti-tuberculous therapy. An extensive review of the literature was made.